ANALISIS VALUE FOR MONEY PADA KINERJA KEUANGAN PEMERINTAH KOTA PONTIANAK TAHUN 2017-2022 - Ramadhannisa, Ifanka (Jurusan Akuntansi FEB UNTAN, 2024)
It is important for local governments to manage regional budgets properly in order to achieve optimal financial performance and provide maximum benefits for the community. This research aims to measure the performance of the Pontianak City Government using the Value For Money methodology in terms of economics, efficiency and effectiveness. The method used in this research is a qualitative descriptive method. Based on the research results, it can be concluded that the performance of the Pontianak City Government as measured using the budget realization report in 2017-2022 is very economical with an average economic ratio of 108.13%. In terms of efficiency, it can be said to be efficient with an average efficiency ratio of 99.29%. In terms of effectiveness, it can be said to be effective with an average effectiveness ratio of 96.07%.